(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to improve the learning outcomes of students in Social Science subjects through the use of differentiated learning strategies on economic activity material. This research is a Classroom Action (PTK) research which is divided into two cycles and begins with a precycle. Each cycle consists of planning, execution, observation and reflection. Research instruments used in this study are teacher activities, student activities, observation of Learning Implementation Plans (RPP) and learning outcomes tests. The data is analyzed descriptively. The criterion for successful action is if 75% of students reach KKM 75. The results of the research show that there is an increase in teacher activity from cycle I to cycle II with a level of 82.5% in cycle I and 90% in cycle II. Student learning activity was 80% in cycle 1 and 92.5 in cycle II. From the data on student learning outcomes, it was found that learning completeness was 67.3% in cycle I and 78.5% in cycle II. From the research data, the average value of students’ learning outcomes using differentiated learning strategies from pre-action to cycle II obtained a significant mastery of learning outcomes, namely 42.8%, so it was concluded that the use of differentiated learning strategies influenced learning outcomes. students in class IV social studies subjects at SDN 2 Cikalang, Tawang District, Tasikmalaya City